Loss of Coilia nasus habitats in Chinese freshwater lakes: An otolith microchemistry assessment - Ly Sokta; Tao Jiang; Hongbo Liu; Zhongya Xuan; Chen Qiu; Xiubao Chen; Jian Yang (Heliyon, 2020)
Loss of valued diadromous fishes and their habitats is one of the most critical problems in aquatic habitat connection and resource management worldwide. In China, the Poyang, Dongting, Gaobao, Gucheng, Dongping, and Taihu lakes were known to be historical migratory spawning sites of the anadromous estuarine tapertail anchovy Coilia nasus. However, except for Poyang Lake, it is believed that these lakes are no longer used by anadromous fish owing to overfishing, water pollution, and loss of connectivity. To confirm this assumption, we used an electron probe microanalyzer to analyze elemental strontium (Sr) and calcium (Ca) microchemical patterns in the otoliths of C. nasus individuals sampled from these lakes, in accordance with our previous analysis of the otolithic patterns of the same species sampled from habitat areas characterized by different salinity gradients. The results of line transect analysis of Sr/Ca ratios and Sr X-ray intensity maps of the otoliths indicated that all individuals from Dongting, Gaobao, Gucheng, Taihu, and Dongping lakes were characterized by a freshwater-resident life history. In contrast, individuals from Poyang Lake exhibited both freshwater-resident and anadromous life histories. The findings of this pilot study suggest that anadromous C. nasus can be found in Poyang Lake but are unlikely to be found in Dongting, Gaobao, Gucheng, Dongping, or Taihu lakes, despite these lakes being historical distribution areas or even spawning sites. This anchovy can possibly be used as a good model species for understanding the aforementioned global problem. Given that C. nasus is a commercially important species, restoration of its natural habitats and maintenance of their connections are recommended for its management and conservation.